2008
DOI: 10.1186/1471-2407-8-110
|View full text |Cite
|
Sign up to set email alerts
|

Methylation alterations are not a major cause of PTTG1 missregulation

Abstract: Background: On its physiological cellular context, PTTG1 controls sister chromatid segregation during mitosis. Within its crosstalk to the cellular arrest machinery, relies a checkpoint of integrity for which gained the over name of securin. PTTG1 was found to promote malignant transformation in 3T3 fibroblasts, and further found to be overexpressed in different tumor types. More recently, PTTG1 has been also related to different processes such as DNA repair and found to trans-activate different cellular pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Epigenetic studies using prostate cancer cell lines suggest that neither methylation status nor loss of heterozygosity is responsible for the altered expression of PTTG1 in tumours (Ref. 51). Histone acetylation modification has recently been implicated in PTTG1 regulation.…”
Section: Regulation Of Pttg Expressionmentioning
confidence: 99%
“…Epigenetic studies using prostate cancer cell lines suggest that neither methylation status nor loss of heterozygosity is responsible for the altered expression of PTTG1 in tumours (Ref. 51). Histone acetylation modification has recently been implicated in PTTG1 regulation.…”
Section: Regulation Of Pttg Expressionmentioning
confidence: 99%
“…Sequencing scan in sixteen human pituitary adenoma biopsies failed to identify any promoter mutation of the Securin gene and therefore it is believed that promoter mutation does not play any role for its enhanced expression [38,39]. Further, no loss of heterozygosity has been reported for the region mapping the PTTG1/Securin locus [39].…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing scan in sixteen human pituitary adenoma biopsies failed to identify any promoter mutation of the Securin gene and therefore it is believed that promoter mutation does not play any role for its enhanced expression [38,39]. Further, no loss of heterozygosity has been reported for the region mapping the PTTG1/Securin locus [39]. In a separate study, it was demonstrated that RAN-alkaloids create more relaxed chromatin structure by altering poly-ADP-ribosylation of cellular proteins which could be considered as a causative factor for RAN-induced carcinogenesis [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Kanakis D et al [ 20 ] failed to find any mutations in the main promoter region of PTTG1 which may result in the overexpression of the PTTG1. Another study on the genetic changes of PTTG1 also excluded methylation and LOH as causes of PTTG1 aberration in human cancers [ 21 ]. miRNAs are small non-coding RNA which participate in a wide array of cellular processes [ 22 ].…”
Section: Introductionmentioning
confidence: 99%